The skin I'm in - Flake, Sharon (New York : Jump at the Sun/Hyperion Books for Children, 1998)
Thirteen-year-old Maleeka, uncomfortable because her skin is extremely dark, meets a new teacher with a birthmark on her face and makes some discoveries about how to love who she is and what she looks like.
670
Accelerated Reader AR
Keywords: African Americans -- Juvenile fiction; Self-esteem -- Juvenile fiction; Teachers -- Juvenile fiction; Schools -- Juvenile fiction